BUSINESS PLAN SEBAGAI IMPLEMENTASI KEWIRAUSAHAAN PADA PEMBELAJARAN EKONOMI DI SMA - Sri Endah Setiarini (Dinamika Pendidikan)
The purpose of this study was to investigate the implementation of business plan on the materials of Entrepreneurship in Economics Studies at SMA Negeri 1 Wonosobo. The respondents were all students of class X at SMA Negeri 1 Wonosobo. The data were collected by observation, interviews and questionnaires. Then, the data were analyzed descriptively. The result of the research showed that 10th grade students at SMA Negeri 1 Wonosobo have implemented entrepreneurial spirit by composing the business plan.